Targeting high transcriptional control activity of long mononucleotide A-T repeats in cancer by Argonaute 1 - Pin-on, Piyapat; Aporntewan, Chatchawit; Siriluksana, Jirattha; Bhummaphan, Narumol; Chanvorachote, Pithi; Mutirangura, Apiwat (My University, 2019)
Epigenetic regulatory changes alter the gene regulation function of DNA repeat elements in cancer and consequently promote malignant phenotypes. Some short tandem repeat sequences, distributed throughout the human genome, can play a role as cis-regulatory elements of the genes. Distributions of tandem long (≥10) and short (<10) A-T repeats in the genome are different depending on gene functions. Long repeats are more commonly found in housekeeping genes and may regulate genes in harmonious fashion. Mononucleotide A-repeats around transcription start sites interact with Argonaute proteins (AGOs) to regulate gene expression. miRNA-bound AGO alterations in cancer have been reported; consequently, these changes would affect genes containing mononucleotide A- and T-repeats. Here, we showed an unprecedented hallmark of gene regulation in cancer. We evaluated the gene expression profiles reported in the Gene Expression Omnibus and found a high density of 13–27 A-T repeats in the up-regulated genes in malignancies derived from the bladder, cervix, head and neck, ovary, vulva, breast, colon, liver, lung, prostate, kidney, thyroid, adrenal gland, bone, blood cells, muscle and brain. Transfection of cell-penetrating protein tag AGO1 containing poly uracils (CPP-AGO1-polyUs) to the lung cancer cell lines altered gene regulation depending on the presence of long A-T repeats. CPP-AGO1-polyUs limited cell proliferation and the ability of a cancer cell to grow into a colony in lung cancer cell lines. In conclusion, long A-T repeats up-regulated many genes in cancer that can be targeted by AGO1 to change the expression of many genes and limited cancer growth.
Keywords: Argonaute proteins; cis-Regulatory elements; Hallmark of cancer; Mononucleotide A-T repeats; Universal target